A sports manager’s key competences model - I. A. Udzhukhu; F. A. Tuguz; E. S. Dvoynikova (Вестник Майкопского государственного технологического университета, 2025)
Introduction. One of the most important criteria for the functioning of a physical education and sports organization is the level of professionalism of its management personnel and, accordingly, the degree of the formation of their competencies. High professionalism of the head of any physical education and sports organization is considered the key to its success. In this regard, the problem of the research is to find optimal ways to form the key competencies of sports managers, which is a pressing scientific problem in the functioning of the modern market of physical education and sports services.Materials and methods. A set of methods of scientific knowledge: analysis, classification, modeling, generalization, visual presentation of data has been used. The theoretical basis of the research is presented by modern conceptual approaches to the professional activity of a sports manager, the parameters of his/her personal and professional characteristics, as well as the organization of pedagogical activity to form his/her key competencies.The results of the research are: clarification of the concept of «sports manager» from the standpoint of his/her professional functions and key competencies; substantiation and development, based on current theoretical and methodological provisions, of a model for the formation of key competencies of a sports manager, ensuring productive activities in managing a sports organization.Discussion and conclusion. A sports manager is considered to be the management team of a physical education and sports organization, whose competence mainly includes issues of organizing and planning the activities of a sports organization. An effective process of managing a sports organization is possible with the development and implementation of the author’s pedagogical model for the formation of key competencies of a sports manager into the system of training and retraining of specialists in the management team, which ensures the development of professional and personal qualities of sports managers and includes three blocks: target, methodological and substantive ones.